Influence of TIO2 nanoparticles on energy efficiency of refrigerators using isobutene as working fluid - Кулешов, Денис Константинович (Eastern-European Journal of Enterprise Technologies, 2014)
The practical aspects of using a mixture of R600a/TiO2 in refrigerators were considered. The experimental studies on the refrigerator characteristics running with the compressor BOCK F2-NH3 were conducted. The results showed that a mixture of R600a/TiO2 can work effectively in the refrigerator. The addition of nanoparticles leads to the improvement of the thermophysical properties and heat transfer characteristics of the refrigerant. In comparison with a refrigerator that uses pure R600a as a refrigerant, the use of TiO2-R600a of 0.1 and 0.5 g/L can reduce energy consumption by 6 % and 8 % respectively. The energy consumption test was performed for comparing the refrigerator performance with a nanorefrigerant and a pure refrigerant to provide the basic data for the use of nanoparticles in refrigeration systems. This research showed that nanoparticles can improve the refrigerator efficiency factor.